Knee Movement Characteristics of Basketball Players in Landing Tasks Before Onset of Patellar Tendinopathy: A Prospective Study - Feng, Ru; Best, Thomas M.; Wang, Lin; Gao, Weiwei; Liu, Hui; Yu, Bing (Frontiers in Sports and Active Living, 2022)
Background: Patellar tendinopathy is one of the most common injuries for basketball players. Jumping and landing movement patterns are potential risk factors for patellar tendinopathy. Hypothesis: During the stop jump, participants who developed patellar tendinopathy would demonstrate greater peak vertical ground reaction force and maximal knee flexion angular velocity, with reduced knee flexion range of motion and knee flexion angles at initial contact prior to the development of the injury. Study Design: Prospective cohort study. Methods: Freshmen college basketball male players (n = 181) were recruited for three consecutive years, and followed to the end of the third year of the study. Three-dimensional kinematic and kinetic data during a stop-jump task were collected for all participants at the beginning of each fall semester. Peak vertical ground reaction force, knee flexion angle at initial foot contact with the ground, range of motion for knee flexion and maximal knee flexion angular velocity during the landing phases of the stop-jump task were reduced. Development of patellar tendinopathy was monitored in follow-up. A two-way ANOVA compared movement patterns between injury and no injury groups and among school years. Results: A total of 60 knees developed patellar tendinopathy. The injury group had a significantly greater peak vertical ground reaction force (P = 0.040), smaller knee flexion angle at initial contact (P = 0.001) and greater maximum knee flexion angular velocity (P = 0.001) during the horizontal landing phase compared to the no injury group. Conclusion: Male basketball players who developed patella tendinopathy demonstrated different characteristics in maximum vertical ground vertical force, knee flexion angle at initial foot contact, and maximum knee flexion angular velocity during landings in a stop-jump task in different school year compared to their counterpart who did not develop the injury.